Prevalence of low-level viremia in the treatment of chronic hepatitis B in China: a systematic review and meta-analysis - Lu Xie; Pengyu Li; Guangwei Liu; Yanan Liu; Huijun Guo (BMJ Open)
Objectives Low-level viremia (LLV) is a risk factor affecting the prognosis of patients with chronic hepatitis B (CHB). The objective of this study was to systematically assess the prevalence of LLV, thereby providing robust evidence-based medical insights into effective clinical interventions and preventative measures against LLV.Design Systematic review and meta-analysis.Data sources A comprehensive literature search was conducted across various databases, including China National Knowledge Infrastructure, Wanfang Data (Wanfang), China Science And Technology Journal Database (VIP-CSTJ), China Biology Medicine disc (CBMdisc), PubMed, Embase, Web of Science and the Cochrane Library, spanning from the inception of these databases up to 5 January 2024.Eligibility criteria The research type included either a cross-sectional study or a cohort study focusing on the Chinese population, with the outcome being LLV. The languages were limited to both Chinese and English. Studies with any of the following were excluded: subjects with other comorbidities, original articles inaccessible or data unavailable, and duplicate publications.Data extraction and synthesis Literature management used EndNote X9.1, and an information extraction table was created using Microsoft Excel to record research information, including first author, year of publication and study type. The prevalence of LLV was assessed via meta-analysis. Meta-analyses were conducted in RStudio using the ‘metaprop ()’ function. Subgroup analysis and sensitivity analysis were used to identify sources of heterogeneity, and funnel plots and AS-Thompson tests were employed to evaluate publication bias.Results 18 studies, encompassing a total sample of 9773 patients, were included in the analysis. Of these, 3336 patients were identified with LLV. The meta-analysis revealed that the prevalence of LLV among treated CHB patients stands at 33.6% (95% CI 30.2 to 37.0). The antigen status, antiviral treatment regimen (type of drugs and nucleos(t)ide analogues (NAs)), treatment duration, medication adherence and baseline hepatitis B virus DNA levels all affected the prevalence of LLV. Sensitivity analysis further corroborated the stability of these meta-analysis findings. The funnel plot and AS-Thompson test indicated no significant publication bias (t = −0.01, p=0.995).Conclusions The prevalence of LLV among CHB patients was established at 33.7% (95% CI 29.8% to 37.6%). Thus, it is imperative for clinical decision-makers to consider the various influencing factors of LLV when formulating treatment plans in order to mitigate any potential adverse outcomes.